Inhibitory effect of organic acids on human neutrophil myeloperoxidase’s peroxidation, chlorination, and nitration activities - Sarkarati Bahram (Türk Biyokimya Dergisi, 2023)
Myeloperoxidase from polymorphonuclear leukocytes is an important enzyme in oxidative metabolism and has a key role in tissue injuries in oxidative stress and inflammatory conditions. Therefore, its inhibitors have become the focus of studies on new drug development in recent years. The aim of the study was to determine the inhibitory effect of organic acids on the peroxidation, chlorination, and nitration activities of myeloperoxidase.